(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
In this paper are presented methods for wood working milling machining, specially we are going to use samples of pine wood. In the beginning a sculpture surfaces will be designed in a CAD/CAM software Fusion 360 and tool paths will be generated using four different strategies for finishing stage, these are: a) parallel, b) scallop, c) radial and d) pencil. On the upper machining surface of the final physical parts we measure the roughness in order to check the produced quality for each strategy. Each strategy compared according the total machining time, the cutting conditions and the geometric accuracy. Physical models will be produced with the use of a rapid prototyping machine ROLAND MDX- 40A for evaluation and tool path comparison.